Green Synthesis and characterization of the ZnO, CuO and ZnO@CuO, Nanoparticles for antibacterial activity - Alzidi, Alzahraa Fadhel; Nasir, Eman M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In this study, an extract from bamboo leaves was used to prepare ZnO NPs, CuO NPs, and ZnO/CuO NPs in a safe, efficient, and eco-friendly manner to reduce the toxicity of nanomaterials and their use in medical applications. XRD analysis confirmed the crystalline nature of the synthesized nanoparticles. The average crystalline size was 22 nm for ZnO, 13.8 nm for CuO, and 14.7 nm for the CuO-ZnO composite. ZnO nanoparticles were hexagonal, while CuO nanoparticles were monoclinic. FESEM demonstrated that the produced nanoparticles were formed in various configurations, combining spherical flower shapes with nanorods with sizes ranging from 30 to 60 nm, which promotes the creation of images and nanoparticles. EDX analysis verified that all samples contained the elements that were present (O, Zn, and Cu). UV-Vis was used to calculate the ZnO, CuO, and ZnO/CuO energy gaps are 4.2 eV, 3.08 eV, and (3.26, 3.72 ) eV, respectively. Additionally, the investigation found that the extract from bamboo leaves included functional groups that serve as agents that reduce and cap. Furthermore, ZnO NPs, CuO NPs, and ZnO/CuO nanocomposites showed great stability at 76.8, 57.2, and 71.6, respectively, according to zeta potential. The study revealed that the material demonstrates greater antibacterial activity against Gram-negative bacteria compared to Gram-positive ones